Stomal variceal haemorrhage in ileal conduit diversion: a rare case report and literature review - Xu, Mingjie; Lin, Yiwei; Shen, Bohua (Frontiers in Oncology, 2024)
BackgroundRadical cystectomy is typically recommended for managing bladder cancer, with ileal conduit diversion being a prevalent form of urinary diversion. Stomal variceal haemorrhage is a rare complication of ileal bladder diversion and poses diagnostic and therapeutic challenges that can escalate to life-threatening circumstances. Hepatic cirrhosis and cancer liver metastasis-induced portal hypertension are considered the main causes of stomal varices. However, the real-world expertise in the pathophysiology of, diagnostic approach to, and overall management strategy for stomal variceal haemorrhage in ileal conduit diversion is limited.Case presentationHerein, we present a rare case of a 77-year-old man with bladder cancer who developed stomal variceal haemorrhage after undergoing radical cystectomy and ileal conduit urinary diversion. Imaging revealed that the peristomal varices communicated with the subcutaneous veins of the abdominal wall without apparent portal hypertension. Transhepatic coil embolization of bleeding stomal varices was successfully performed via a transhepatic antegrade approach. No complications or stomal variceal haemorrhage occurred during a 6-month follow-up period.ConclusionTranshepatic coil embolization may be considered an initial therapeutic option for patients who experience stomal variceal haemorrhage. Comprehensive management of underlying liver disease and portal hypertension is needed at follow-up visits. We describe successful experience with the precise treatment of this rare and atypical disease, conduct a thorough review of the pertinent literature, and deliberate on optimized diagnostic and therapeutic procedures.